China's coordinated tripartite medical reform: strategic balancing of interests among pharmaceuticals, healthcare, and health insurance - Gong, Hanxiang; Wu, Wenbo; Li, Jifeng; Wu, Baoling; Gao, Mengqi; Yang, Yajun (Frontiers in Public Health, 2025)
China has implemented the “Triple-Medical” reform, aiming to enhance the overall efficacy of the public healthcare system through deep integration and coordination among healthcare, pharmaceuticals, and health insurance regulator. This study utilizes game theory to analyze the strategic interplay and conflicts of interest among these three sectors within China's reform context, exploring the strategic choices and interactions that occur during the reform process. This study utilizes game theory to analyze the strategic interplay among pharmaceutical companies, healthcare institutions, and the health insurance regulator in China's healthcare reform. The model examines key variables and behaviors of each stakeholder, with MATLAB simulations analyzing evolutionarily stable strategies and parameter sensitivity. The findings reveal complex dynamic interactions among the strategies adopted by the various stakeholders within the healthcare reform, with the optimal strategies converging at the equilibrium point. Specifically, pharmaceutical companies seek maximum economic gains through drug pricing and quality control; healthcare institutions strive to enhance service efficiency and quality to meet patient needs; and medical insurance regulatory bodies play a crucial role in ensuring the efficiency and fairness of fund utilization. Such strategic alignments contribute to the stable operation of the healthcare system and maximize the interests of all parties involved. The study concludes that coordinated strategies among pharmaceutical companies, healthcare institutions, and health insurance regulator can achieve equilibrium and enhance the efficiency and equity of China's healthcare system. Changes in penalties for pharmaceutical companies, costs of medical service quality, and medical insurance regulatory costs critically influence healthcare reform, providing empirical support and a theoretical basis for effective policy-making. Refining policy adjustments and strategic optimizations can effectively coordinate the interests of all parties, propelling China's healthcare system toward greater efficiency and fairness.